KONTROL DIRI TERHADAP PERILAKU KONSUMTIF SISWA SISWI SMK AL-HIKMAH CURUG - Alya Juniar, Syifa (Universitas Islam Syekh Yusuf, 2023)
Self control is an individual's ability to control, control and restrain one's own desires in carrying out an action, being able to manage behavior according to situations and conditions, and having high sensitivity towards oneself, other people and the surrounding environment. Today's students are often unable to restrain or control themselves, so everything they want must be fulfilled, which can result in consumer behavior. The aim of this research is to identify the relationship between self-control and consumer behavior among female students at Al-Hikmah Curug Vocational School.